2022
DOI: 10.3389/fmed.2022.1078237
|View full text |Cite
|
Sign up to set email alerts
|

Clinical presentation of acute primary angle closure during the COVID-19 epidemic lockdown

Abstract: PurposeThis study aimed to investigate the clinical presentation of acute primary angle closure (APAC) during the COVID-19 epidemic lockdown in Wuhan.MethodsConsecutive patients seeking APAC treatment at the Wuhan Aier Eye Hospital during the 76 days (January 23–April 8, 2020) when the lockdown policy was implemented due to the COVID-19 pandemic were compared to those during the same period the following year (January 23–April 8, 2021), when the lockdown policy was not implemented. The cohorts were compared to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 35 publications
1
6
0
Order By: Relevance
“… 16 During Wuhan’s COVID-19 pandemic from the end of 2019 to the beginning of 2020, a mild increase in the number of APAC cases was observed compared to the next year. 26 Our study showed an obvious outbreak of APAC cases in clinics during the COVID-19 Omicron variant pandemic, which is comparable with a recent report from other hospital in Shanghai and Guangdong. 27 , 28 This may be due to the higher prevalence of PACG among Eskimos, Chinese, and Mongolians.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“… 16 During Wuhan’s COVID-19 pandemic from the end of 2019 to the beginning of 2020, a mild increase in the number of APAC cases was observed compared to the next year. 26 Our study showed an obvious outbreak of APAC cases in clinics during the COVID-19 Omicron variant pandemic, which is comparable with a recent report from other hospital in Shanghai and Guangdong. 27 , 28 This may be due to the higher prevalence of PACG among Eskimos, Chinese, and Mongolians.…”
Section: Discussionsupporting
confidence: 90%
“…Additionally, these data are very similar to those of previous reports in China or Korea in the non-pandemic period. 26 , 35–37 However, the time from symptoms to treatment in the pandemic group was 7.92 ± 6.14 days, which was significantly longer than that in the control group (3.63 ± 2.93 days). In the pandemic group, the time from symptoms to treatment in COVID-19-positive patients was 8.42 ± 6.21 days, which was longer than that in COVID-19-negative patients (6.55 ± 5.76 days).…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…Zhou et al conducted a comparative analysis of APAC cases during the COVID-19 lockdown period and the corresponding period in the subsequent year. [ 14 ] Their study revealed that during the lockdown, patients experienced a prolonged duration from symptom onset to treatment initiation and presented with elevated IOP. In contrast, our investigation did not identify a significant variation in the disease course between the 2 cohorts.…”
Section: Discussionmentioning
confidence: 99%
“…While previous case reports and studies have explored the occurrence of APAC attacks during the COVID-19 pandemic, most of them were based on a small number of cases or focused on the clinical characteristics of APAC during lockdown. [12][13][14][15] However, the potential risk factors and clinical characteristics of APAC patients during a COVID-19 outbreak without lockdown remain unexplored. Our investigation assumes that the systemic inflammation and vascular abnormalities associated with COVID-19 may contribute to the pathophysiology of APAC, either by exacerbating preexisting conditions or by initiating new pathogenic processes in the eye.…”
Section: The Authors Have No Conflicts Of Interest To Disclosementioning
confidence: 99%